Optimal Decision Making Through Return On Time Analysis For The Venture Capital Industry - Tucker, Steve (2007)
Venture capital firms make capital investments in businesses in return for an equity stake. However finding businesses that deliver the kind of returns venture capital firms seek is not a straight forward task. This undertaking is made all the more difficult when investing in a start up business which has no track record.